Offshoring: understanding the emerging global labor market - Farrell, Diana (ed.) (Boston, 2006)
This book provides an authoritative perspective on offshoring from McKinsey & Company. Offshoring is an evolving issue full of minefields and new developments. It is a business tool and an economic phenomenon with significant potential to increase the world's wealth. But it also changes the structural dynamic of companies that employ it and increases the pace of change in the societies that it affects. These issues all need to be carefully managed if the economic benefits from offshoring are to translate into net gains in developed and emerging markets. This anthology aims to help decision makers manage offshoring better. Over the past four years, the McKinsey Global Institute (MGI) has been studying offshoring intensively. The goal of this anthology is to give decision-makers and shapers in government and business a better understanding of the scope and economics of offshoring as well as its effects, so they can test their opinions against facts, and plan more strategically. This volume presents what McKinsey considers their most substantial contributions to the offshoring debate, including ten of MGI's published articles on the topic.
Keywords: Global labour market